P09-12: Exploring the regulatory effects of lysine acetylation and phosphorylation in adipocyte differentiation and their exposure to emerging plastic additives - A.S. Aldehoff; I. Karkossa; B. Engelmann; U. Rolle-Kampczyk; M. von Bergen; K. Schubert (Toxicology Letters, 2023)

The role of phase transition by inception and surface reactions for the synthesis of silicon nanoparticles in a hot-wall reactor – Simulation and experiment - P. Wollny; L. Engelmann; M. Loewenich; I. Rahinov; H. Wiggers; C. Schulz; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

The role of phase transition by nucleation, condensation, and evaporation for the synthesis of silicon nanoparticles in a microwave plasma reactor — Simulation and experiment - P. Wollny; J. Menser; L. Engelmann; J. Sellmann; C. Schulz; H. Wiggers; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Evaluation of different samplers and storage temperature effect on the methane carbon stable isotope analysis - Victor H. J. M. dos Santos; Diane O. Laroque; Caroline I. Baum; Pâmela de M. Engelmann; Rogério V. Lourega; Luiz F. Rodrigues (Environmental Monitoring and Assessment, 2018)

Genetic makeup of Shiga toxin-producing Escherichia coli in relation to clinical symptoms and duration of shedding: a microarray analysis of isolates from Swedish children - A. Matussek; C. Jernberg; I.-M. Einemo; S. Monecke; R. Ehricht; I. Engelmann; S. Löfgren; S. Mernelius (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Voltammetric studies of Zn and Fe complexes of EDTA: Evidence for the push mechanism - Ryan M. Hutcheson; Mark D. Engelmann; I. Francis Cheng (BioMetals, 2005)

A hypothesis for the basis of the pro-oxidant nature of calcium ions - Ryan Hutcheson; Mark D. Engelmann; I. Francis Cheng (BioMetals, 2004)

Viral Lower Respiratory Tract Infection in the Elderly: A Prospective In-Hospital Study - J. Flamaing; I. Engelmann; E. Joosten; M. Van Ranst; J. Verhaegen; W. E. Peetermans (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Variability of the Fenton reaction characteristics of the EDTA, DTPA, and citrate complexes of iron - Mark D. Engelmann; Robert T. Bobier; Terrance Hiatt; I. Francis Cheng (BioMetals, 2003)